2005
DOI: 10.1029/2004jc002522
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of long sea‐level time series in the northern coast of Spain

Abstract: [1] Sea-level time series recorded at three stations of the northern Spanish coast (Santander, Coruña, and Vigo) are examined with the aim of obtaining reliable interdecadal trends. The records are about 6 decades long, and their consistency is checked by means of an Empirical Orthogonal Function (EOF) analysis. Major benefits of the analysis are the detection of undocumented changes of sea-level reference and the filling of data gaps. For the last decade, the consistency of the trends is also checked against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 19 publications
2
32
1
5
Order By: Relevance
“…The results were independent of the fitting method used by the different authors. The values observed for Vigo were larger than those reported in previous studies (Douglas 2001, Peltier 2001 ) by Marcos et al (2005). The reason for the observed discrepancies should be analyzed in detail.…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…The results were independent of the fitting method used by the different authors. The values observed for Vigo were larger than those reported in previous studies (Douglas 2001, Peltier 2001 ) by Marcos et al (2005). The reason for the observed discrepancies should be analyzed in detail.…”
Section: Resultscontrasting
confidence: 52%
“…It is commonly accepted that the global sea level has been rising at a rate of 1.5 to 2.0 cm decade -1 during the last century (e.g. ously used by different authors to identify sea level patterns around the IP (Cabanas et al 2003, Marcos et al 2005, Rosón et al 2009). In the present study we used the gauges located at Coruña and Vigo harbors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of sea level records from the tide gauge of Santander, located in the SE Bay of Biscay, has revealed that relative mean sea-level has been rising at a rate of 2.08 ± 0.33 m m yr-1, from 1943 to 2004 (Chust et al, 2009); this is consistent with sea-level trends from other tide-gauge measurements within the area and with previous results obtained in the Bay of Biscay (Marcos et al, 2005). The mean sea level in the bay is expected to rise between 29 and 49 cm from 2001 to 2099, as estimated from Atmosphere-Ocean Coupled General Climate Models (AOGCMs) outputs as a result of regional thermal expansion and global ice-melting (Chust et al, 2010).…”
Section: Introductionsupporting
confidence: 77%
“…Several studies, within the southern Bay of Biscay, have identified a sea level rise (SLR) during the second half of the 20th century (Marcos et al, 2005). An analysis of sea level records from the tide gauge of Santander, located in the SE Bay of Biscay, has revealed that relative mean sea-level has been rising at a rate of 2.08 ± 0.33 m m yr-1, from 1943 to 2004 (Chust et al, 2009); this is consistent with sea-level trends from other tide-gauge measurements within the area and with previous results obtained in the Bay of Biscay (Marcos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%